An SDILINE profile oriented to patient care. - Funk, M E (1978)
Hospital physicians naturally require current medical information in order to treat their patients. An objectively obtained SDILINE storesearch was devised to obtain this information. A rank-ordered list of hospital discharge diagnoses, coded with ICDA terms, was translated into MeSH. The top two Bradford zones of journals defined as useful at the University of Missouri--Kansas City were ANDed to these MeSH terms. Citations retrieved from the storesearch are input into an in-house computerized data base. The method can be easily used by other medical or hospital libraries without access to computers.